Genetic variability and divergence in okra (Abelmoschus esculentus) - Singh, R K; Rai, Mritunjay; Kumar, Arvind; Dwivedi, S V; Kumar, Mukul (Current Horticulture, 2023)
An experiment comprising 19 genotypes of okra {Abelmoschus esculentus (L.) Moench} sown in RBD with three replications was conducted during rainy season of 2019 and 2020 at Vegetable Research Farm, BUAT Banda. The genotypic coefficient of variation (GCV) and phenotypic coefficient of variation (PCV) were highest for days to 50% germination and lowest for first flower, days to 50% flower, days to maturity, fruit length, fruit diameter, number of seeds/fruit, fruit yield/plant, fruit yield/plot and fruit yield. The heritability estimates were high for days to 50% germination, average fruit weight, number of fruits/plant, fruit yield/ plant and fruit yield, indicating that selection based on phenotypic performance would be more operative. The high heritability coupled with high GAM was observed for days to 50% germination, average fruit weight and number of fruits/plant, indicating that additive gene effect was more important. Based on D2 analysis, 19 genotypes were grouped into six clusters. The cluster I had seven genotypes followed by cluster II and III with six and three genotypes respectively, while the remaining clusters were monogenotypic. The cluster II recorded maximum intra cluster distance, followed by cluster I and clusters III. Maximum inter-cluster distance was observed between cluster III and VI, followed by that between cluster III and IV and between cluster I and III, suggesting that genotypes belonging to cluster III and VI, III and IV and I and III are more divergent than the rest of the clusters.